2009
DOI: 10.1007/s12206-009-0101-5
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of deformations of steel plate by artificial neural network in forming process with induction heating

Abstract: To control a heat source easily in the forming process of steel plate with heating, the electro-magnetic induction process has been used as a substitute of the flame heating process. However, only few studies have analyzed the deformation of a workpiece in the induction heating process by using a mathematical model. This is mainly due to the difficulty of modeling the heat flux from the inductor traveling on the conductive plate during the induction process. In this study, the heat flux distribution over a ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…With regard to such a line heating forming approach, Ueda et al (1991Ueda et al ( , 1993Ueda et al ( , 1994a predicted line heating forming paths based on the inherent strain calculation. And Nguyen et al (2009) used artificial neural networks to carry out similar studies. Based on theoretical studies, automation equipment adopting the line heating forming approach has been successfully developed so that the processing efficiency for hull plates can be effectively improved (Yoshihiko et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to such a line heating forming approach, Ueda et al (1991Ueda et al ( , 1993Ueda et al ( , 1994a predicted line heating forming paths based on the inherent strain calculation. And Nguyen et al (2009) used artificial neural networks to carry out similar studies. Based on theoretical studies, automation equipment adopting the line heating forming approach has been successfully developed so that the processing efficiency for hull plates can be effectively improved (Yoshihiko et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study an attempt has been made towards the applications of ANN system in modeling the processing route with predictability of the systems parameters in induction line heating [2,3]. They are being used in the areas of prediction and classification, areas where nonlinear models and other related statistical techniques have traditionally been used.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, research has shown that a travelling induction coil can also be used to bend steel plate in a forming process [17,18]. These studies determined that the bending distortion caused in the process is predictable and, similar to welding, the bending effect is primarily influenced by the travel speed of the coil (the heat input) and the thickness of the plate.…”
mentioning
confidence: 99%
“…ANN models have also been employed to predict the bending behaviour of steel when subjected to heating with a travelling induction coil [18]. The model produced by Ngyuyen et al [18] considered the bending produced by induction heating on unwelded steel plates and demonstrated the ability of ANNs to accurately predict the resulting distortion based upon a given set of heating parameters.…”
mentioning
confidence: 99%
See 1 more Smart Citation